Karakterisasi Minyak Jelantah Hasil Produksi Keripik Nenas Dengan Metode Vacuum Frying - Rusdianasari Rusdianasari; Leila kalsum; Aida Syarif; Yohandri Bow (Politeknik Negeri Sriwijaya, 2019)
Small and medium businesses (SMEs) have developed rapidly in Indonesia, especially for the food sector. One of the most productive UKM in Prabumulih city is UKM Melati which produces pineapple chips from pineapple which is a regional superior product from Prabumulih city. To get dried and tasty pineapple chips, frying is done by using a vacuum frying method that requires a lot of cooking oil. The results of vacuum drying frying will produce used browning frying oil or used cooking oil and cannot be reused if the characteristics of used cooking oil exceed the standard. For this reason, an analysis is needed to determine the characteristics of used cooking oil from the results of the production of pineapple chip vacuum vacuum frying methods. From the results of the analysis that has been carried out on filtered used cooking oil, the value of free fatty acid (FFA) is 4.9% (maximum requirement 0.3%) and peroxide value 1.8 Meq/kg. Thus, used cooking oil cannot be used anymore for frying.